1987
DOI: 10.1038/330752a0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation fails to activate chloride channels from cystic fibrosis airway cells

Abstract: Chloride impermeability of epithelial cells can account for many of the experimental and clinical manifestations of cystic fibrosis (CF). Activation of apical-membrane Cl- channels by cyclic AMP-mediated stimuli is defective in CF airway epithelial cells, despite normal agonist-induced increases in cellular cAMP levels. This defect in Cl- channel regulation has been localized to the apical membrane by exposing the cytoplasmic surface of excised membrane patches to the catalytic subunit (C subunit) of cAMP-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
108
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(121 citation statements)
references
References 0 publications
10
108
2
Order By: Relevance
“…In some preparations, outward rectifiers can be activated in cell-attached patches by CAMP and may therefore contribute to apical Cl conductance . This proposed role, and its relevance to CF, is supported by reports that outward rectifiers excised from normal cells can be activated by exposure to A-or C-kinase whereas those from CF cells are not responsive [16,17].…”
Section: The Pathways Responsible For Apical CL Conductancesupporting
confidence: 51%
“…In some preparations, outward rectifiers can be activated in cell-attached patches by CAMP and may therefore contribute to apical Cl conductance . This proposed role, and its relevance to CF, is supported by reports that outward rectifiers excised from normal cells can be activated by exposure to A-or C-kinase whereas those from CF cells are not responsive [16,17].…”
Section: The Pathways Responsible For Apical CL Conductancesupporting
confidence: 51%
“…Modulation by phosphorylation which is common to many other ion channels, both ligand-and voltage-gated, is rather absolute in the case of CFTR [22] and may be required for propagation of the conformational impact of ligand binding to the pore. Patch-clamp studies with CF epithelial cells in the 1980s before the discovery of CFTR indicated a defective cAMP-stimulated anion current [35,66] and the CFTR sequence later revealed the presence of a large cluster of consensus sites for phosphorylation by cAMPdependent protein kinase A in the R domain [63]. Extensive studies have confirmed that the phosphorylation state of these sites strictly controls the activity of the CFTR chloride channel [12,48].…”
Section: Cftr Control By Phosphorylationmentioning
confidence: 99%
“…This aspect of epithelial function is essential for rehydration of airway mucus. Abnormalities in the Cl conductance pathway also appear critical to disease processes such as those occurring in cystic fibrosis (11,12).Phenotypic characteristics have been well maintained in SV40-transformed fibroblasts (13-15). In SV40-transformed epithelial cells (16)(17)(18)(19), certain aspects of phenotype are retained better than others (17,18,20,21).…”
mentioning
confidence: 99%